KEPEMIMPINAN KEPALA MADRASAH DALAM UPAYA MENINGKATKAN KINERJA GURU DI MTS PP RAUDHATUSSALAM MAHATO KABUPATEN ROKAN HULU PROVINSI RIAU TAHUN PELAJARAN 2024-2025 - Saputra, Nirwan Winata; Abun, Ahmad Rifai; Linda, Rita (UNISAN JURNAL, 2026)
This research aims to describe and analyze the leadership of the head of the madrasah in efforts to improve teacher performance at MTs PP Raudhatussalam Mahato, Rokan Hulu Regency, Riau Province, in the 2024–2025 academic year. This study employs a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation. The results indicate that the head of the madrasah adopts a transformational and participative leadership style, demonstrated by active involvement in guiding, motivating, and encouraging teachers to enhance their competencies and work ethics. The strategies implemented include regular academic supervision, professional teacher development, motivation and rewards, enforcement of discipline, and the integration of religious values into educational activities. The challenges faced by the madrasah head include limited educational facilities, teachers’ dual roles, and varying levels of teacher education. However, with a communicative and humanistic leadership approach, these challenges can be addressed effectively. The study concludes that effective, collaborative, and value-oriented leadership significantly contributes to improving teacher performance and fostering a madrasah environment that supports high-quality and spiritually grounded learning.